Ação antimicrobiana da clorexidina gel e líquida e do hipoclorito de sódio - Ferraz, Rodrigo Fernandes Cabral Pais [UNESP] (2013)
The purpose of this study was to evaluate in vitro antimicrobial activity of chlorhexidine gel and liquid 2%, and 2% sodium hypochlorite on Candida albicans, Enterococcus faecalis, Escherichia coli in root canals. For this, we used 40 human single-rooted teeth were divided into 4 groups (n = 10) according to assist the chemical used: 1) 2% chlorhexidine liquid, 2) 2% chlorhexidine gel, 3) sodium hypochlorite 2%, and 4) physiological saline (control). Content were collected immediately after root canal instrumentation and after 7 days of biomechanical. For the samples was conducted to evaluate the antimicrobial activity and the results were subjected to statistical analysis of Kruskal-Wallis and Dunn's test with a significance of 5%. It was found that chlorhexidine gel and liquid as well as sodium hypochlorite were effective against the microorganisms tested